An introduction to genetic and epigenetic changes in prostate gland – implications in efficacy of phytotherapy of benign prostatic hyperplasia and prostate cancer - Bartkowiak-Wieczorek, Joanna; Kujawski, Radosław; Bogacz, Anna; Ożarowski, Marcin (Journal of Medical Science, 2015)
The usage of classical pharmacological treatment of prostate diseases causes the risk of a number of side effects therefore the researchers are looking for new pharmacologically active molecules, including those contained in the plant extracts. The most widely studied is the lipido-sterolic extract from Serenoa repens (saw palmetto), water extract from Camellia sinensis (green tea) and several cruciferous vegetables. The molecular mechanisms underlying of the development and the progression of prostate disorders, especially benign prostatic hyperplasia (BPH) and prostate cancer (PC), remain still poorly understood. The development of pathologically changed prostate cells proliferation involves many factors, including genetic alterations, such as mutations, and epigenetic changes, appear to contribute to the transformation and progression of prostate cancer. In this paper we suggest that the knowledge of epigenetic modifications presented in this paper introduces the new point of view concerning the possibility of action of plant substances used in prevention and symptomatic treatment of BPH and prostate cancer. Thus, identification of the epigenetic modifications involved on the one hand in the development and progression of BPH / PC, on the other influencing the efficacy and safety of potential phytotherapeutics will be helpful in identifying its novel therapeutic strategy.
Keywords: prostate disorders; phytotherapy; epigenetic modifications